Opinion and preference research on typography for children - Rumjanek, Letícia; Lessa, Washington Dias (InfoDesign, 2010)
In regard to legibility research with children starting to learn to read, besides the evaluation of objective parameters related to reading, some authors try to listen to the participants’ opinion and preference concerning the typographic options used in the research. This approach can be carried out both with children and teachers, and it strives for obtaining data that may help in selecting the parameters to be considered in a reading performance test. The investigation of subjective factors, such as the opinion of readers, may bring about new issues to be considered in new studies of the theme, and also a broader comprehension of reading practice. [ Download ]